Sleep and circadian differences between light and heavy adult alcohol drinkers. (31st July 2022) - Burgess, Helen J.; Rizvydeen, Muneer; Kikyo, Fumitaka; Kebbeh, Nema; Tan, Michael; Roecklein, Kathryn A.; Hasler, Brant P.; King, Andrea C.; Cao, Dingcai
Abstract: Background: Numerous studies have reported that eveningness is associated with increased alcohol consumption. However, biological markers of circadian timing, such as dim light melatonin onset (DLMO) and circadian photoreceptor responsivity (post‐illumination pupil response, PIPR), have rarely been assessed in the context of habitual alcohol consumption. This study aimed to examine sleep, circadian timing, and photoreceptor responsivity in adult alcohol drinkers. Methods: Participants (21 to 45 years) included 28 light and 50 heavy drinkers. The 8‐day study consisted of a week of ad lib sleep monitored with wrist actigraphy, followed by a 9‐h laboratory session with a photoreceptor responsivity and circadian phase assessment. Results: The heavy drinkers obtained on average 28 more minutes of sleep ( p = 0.002) and reported more eveningness than the light drinkers ( p = 0.029). There was a trend for a shorter DLMO‐midsleep interval ( p = 0.059) in the heavy drinkers, reflecting a tendency for them to sleep at an earlier circadian phase. The PIPR in the heavy drinkers was significantly smaller than in the light drinkers ( p = 0.032), suggesting reduced circadian photoreceptor responsivity in the heavy drinkers. A larger PIPR was significantly associated with a later DLMO in the light drinkers ( r = 0.44, p = 0.019), but this relationship was absent in the heavy drinkers ( r = −0.01, p = 0.94). Conclusions: These results are consistent with earlier reports of more eveningness and a shorter DLMO‐midsleep interval being associated with heavier alcohol drinking. The novel finding of reduced circadian photoreceptor responsivity in heavy drinkers is consistent with prior rodent studies. Future studies should explore the impact of habitual alcohol consumption on other measures of circadian photoreceptor responsivity. Abstract : This study of light and heavy alcohol drinkers found that heavy alcohol drinking was associated with more eveningness, and a trend towards more circadian misalignment, as reflected in a shorter interval between the dim light melatonin onset and midpoint of sleep. Heavy drinking was also associated with reduced circadian responsivity to light, as assessed with the post‐illumination pupil response. The relationship between circadian responsivity to light and circadian timing was also weaker in heavy drinkers than in light drinkers.